A nanoscale iron catalyst for heterogeneous direct N- and C-alkylations of anilines and ketones using alcohols under hydrogen autotransfer conditions. Issue 58 (3rd July 2019) - Nallagangula, Madhu; Sujatha, Chandragiri; Bhat, Venugopal T.; Namitharan, Kayambu
Abstract : A heterogeneous and commercially available nanoscale iron catalyst for direct N - and C -alkylation reactions of anilines and methylketones with alcohols under hydrogen autotransfer conditions. Abstract : Here, we report a commercially available nanoscale Fe catalyst for heterogeneous direct N - and C -alkylation reactions of anilines and methyl ketones with alcohols. A hydrogen autotransfer mechanism has been found to operate in these reactions by deuterium labelling studies. In addition, dehydrogenative quinoline synthesis has been demonstrated from amino benzyl alcohols and acetophenones.